MicroRNA-132 attenuates cerebral injury by protecting blood-brain-barrier in MCAO mice - Zuo, Xiaokun; Lu, Jianfei; Manaenko, Anatol; Qi, Xin; Tang, Jiping; Mei, Qiyong; Xia, Ying; Hu, Qin (Experimental Neurology, 2019)
MicroRNAs (miRNAs) have been widely reported to induce posttranscriptional gene silencing and led to an explosion of new strategies for the treatment of human disease. It has been reported that the expression of MicroRNA-132 (miR-132) are altered both in the blood and brain after stroke. However, the effect of miR-132 on blood-brain barrier (BBB) disruption in ischemia stroke has not been studied. Here we will investigate the effects of miR-132 on the permeability of BBB after ischemic stroke and explore the potential mechanism underlying observed protection. Eight week-old mice were injected intracerebroventricularly with miR-132, antagomir-132 or agomir negative control (agomir-NC) 2 h before middle cerebral artery occlusion (MCAO), followed by animal behavior tests and infraction volume measurement at 24 h after MCAO. BBB permeability and integrity were measured by Evan's blue extravasation and brain water content. The expression of tight junction proteins was detected by immnostaining and Western blots. The level of MiR-132 and its targeted gene Mmp9 were assayed. Treatment with exogenous MiR-132 (agomir-132) decreased the infraction volume, reduced brain edema, and improved neurological functions compared to control mice. Agomir-132 increased the level of MiR-132 in brain tissue, suppressed the expression of MMP-9 mRNA and decreased the degradation of tight junction proteins VE-cadherin and β-Catenin in ischemic stroke mice. Inhibition of MMP-9 has a similar protective effect to agomir-132 on infraction volume, brain edema, and tight-junction protein expression after MCAO. Our results indicated that miR-132/MMP-9 axis might be a novel therapeutic target for BBB protection in ischemic stroke.
CRIS-Team Scopus Importer:2019-05-02
Keywords: BBB integrity; Ischemic stroke; MicroRNA-132; MMP-9